Directional molecular sliding movement in peptide hydrogels accelerates cell proliferation. Issue 5 (2nd January 2020) - Song, Shuxin; Wang, Jingyu; Cheng, Zhifei; Yang, Zhimou; Shi, Linqi; Yu, Zhilin
Abstract : Dynamic peptide hydrogels undergoing directional domain sliding movement upon release of covalent constraint accelerate cell proliferation through a mechanotransduction pathway. Abstract : Adjusting the mechanical cues generated in cellular microenvironments is important for manipulating cell behaviour. Here we report on mechanically dynamic hydrogels undergoing directional domain sliding motion and investigate the effect of the well-defined mechanical motion on accelerating cell proliferation. The mechanically dynamic hydrogels were prepared via self-assembly of an amphiphilic peptide consisting of two alternating polar and nonpolar domains cross-linked by disulfide bonds at a nonsymmetrical position. The cross-linked peptide assembled into entangled nanofibers driven by the hydrophobic collapse involving a partial-length sequence due to the covalent constraint. Reduction of the disulfide bonds led to formation of non-equilibrated peptide bilayers, which underwent directional domain sliding motion along each promoted by the thermodynamically favourable transition from the partial to full hydrophobic collapse. The mechanical cues resulting from the directional domain sliding motion within the mechanically dynamic hydrogels accelerated cell proliferation when incubating cells on the hydrogel, compared to the thermodynamically static counterparts, via a mechanotransduction mechanism as supported by the facilitated translocation of yes-associated proteins into the nucleus of the cells. Our finding demonstrates the great potential of mechanically dynamic hydrogels as new-generation biomimetic extracellular matrices in tissue engineering and regeneration.